National Policies for Child Nutrition Security and Their Impact on Learning Outcomes - Sulistiani, Tini; Dewi, Harmala; Fitriani, Apriza; Hartati, Merri Sri (PT. Publikasiku Academic Solution, 2026)
The Free Nutritious Meal Program has become a strategic policy that plays an important role in increasing the nutritional security of school children while supporting the success of learning in Indonesia. The program emphasizes the provision of nutritionally balanced, safe, affordable, and data-driven management for effective evaluation. This research uses the method of literature study, reviewing scientific literature, government reports, and the latest international studies (2020–2025) related to the implementation of similar programs in various countries. The results of the study showed that the free nutritious meal program was able to significantly improve children's nutritional status, school attendance, and academic achievement. Factors that determine the success of the program include menu design based on children's nutritional needs, active involvement of local communities, quality control and food safety, and data-based monitoring and evaluation systems. The program also encourages integration between education and school health services, supporting long-term outcomes in terms of improving overall student health, learning ability, and well-being. Thus, the Free Nutritious Meal Program not only meets children's nutritional needs, but also strengthens the synergy of education and health, making it an important instrument in the development of healthy, intelligent, and productive human resources in Indonesia.